2018
DOI: 10.1177/1066896918791031
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid Granuloma of Parotid Gland: A Case Report With Review of the Literature

Abstract: Crystalloid granuloma (CG) of salivary gland is an extremely rare inflammatory disease, and only 6 cases have been reported in the English literature. CG is histologically characterized by a granulomatous reaction to amylase crystalloid deposition. A 73-year-old woman presented with a painful left neck mass. Computed tomography depicted a mass located in the lower pole of the left parotid gland, suspicious for a tumoral lesion. Preoperative fine needle aspiration cytology found amylase crystalloid deposition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Amylase crystalloids are crystalline structures that are variably rhomboid, rectangular, and needlelike in shape that are predominantly associated with nonneoplastic salivary gland disease, such as sialadenitis and benign cysts, but can also be found associated with neoplastic lesions including WT and pleomorphic adenoma. [20][21][22][23][24][25][26][27][28] Amylase crystalloids are likely an underrecognized and underreported finding in cytology (in all 3 cases in the current study cohort, amylase crystalloids were not noted on prospective review). However, their recognition can be helpful especially for FNA cases where a malignant lesion is being considered.…”
Section: Cancer Cytopathology September 2022mentioning
confidence: 98%
“…Amylase crystalloids are crystalline structures that are variably rhomboid, rectangular, and needlelike in shape that are predominantly associated with nonneoplastic salivary gland disease, such as sialadenitis and benign cysts, but can also be found associated with neoplastic lesions including WT and pleomorphic adenoma. [20][21][22][23][24][25][26][27][28] Amylase crystalloids are likely an underrecognized and underreported finding in cytology (in all 3 cases in the current study cohort, amylase crystalloids were not noted on prospective review). However, their recognition can be helpful especially for FNA cases where a malignant lesion is being considered.…”
Section: Cancer Cytopathology September 2022mentioning
confidence: 98%
“…[10][11][12] Amylase crystalloids are mostly associated with nonneoplastic conditions including duct obstruction, sialadenitis, oncocytic cysts or cystadenomas, developmental cysts, and lymphoepithelial cysts. 1,[10][11][12][13][14][15][16][17][18] They have also been reported in association with Warthin tumors, which are benign neoplastic lesions. 1,19 Based on the current literature, amylase crystalloids have not been found in association with malignancy.…”
Section: Amylase Crystalloidsmentioning
confidence: 99%
“…They have been found predominantly in association with nonneoplastic salivary gland disease, which includes sialadenitis, obstructive cysts, and crystalloid granuloma, although they have also rarely been found in association with some neoplastic lesions, including Warthin tumor and pleomorphic adenoma. [2][3][4][5][6][7][8][9] It has been indicated that the presence of a cystic space, which results from salivary stasis, is crucial for the formation of amylase crystalloids, likely because α-amylase becomes condensed in supersaturated saliva and undergoes crystallization in the cystic space. 6,8,9 Tyrosine crystalloids, conversely, have been identified more frequently in association with salivary gland neoplasms, most commonly benign neoplasms and specifically pleomorphic adenomas; however, there have been rare reported cases of tyrosine crystalloids in adenoid cystic carcinoma and polymorphous (low-grade) adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%